Pengetahuan mitigasi dan kapasitas kebencanaan melalui virtual meeting pada mahasiswa magister IPA Universitas Mataram - Kosim Kosim; Makhrus Muhamad; Aliefman Hakim (Rengganis Jurnal Pengabdian Masyarakat, 2021)
NTB Province is one of the areas prone to natural disasters. In 2018 there was an earthquake that destroyed infrastructure and the safety of human life. The number of casualties due to the earthquake, one of which is the lack of public knowledge about disasters. Through counseling, the increase in knowledge and capacity to reduce disaster risk in science master students at the University of Mataram. It is hoped that students as intellectual agents in the community can continue or inform their environment. Data collection methods: before and after counseling, students were given a questionnaire via google form sent via WA regarding a) disaster knowledge, b) disaster risk reduction capacity and c) disaster mitigation measures. The discussion is more devoted to earthquake disasters. Outreach was held on November 5, 2020 virtually via zoom meeting. The number of participants who took part was 45 people, consisting of 16 male students and 29 female students. The results show that it is not satisfactory, because the percentage increase in knowledge at the high level is still smaller than the percentage level at the lower level. Therefore, it is suggested that education about disaster risk capacity still needs to be disseminated.